2016
DOI: 10.1080/23328940.2015.1131506
|View full text |Cite
|
Sign up to set email alerts
|

Body temperature regulation in diabetes

Abstract: The effects of type 1 and type 2 diabetes on the body's physiological response to thermal stress is a relatively new topic in research. Diabetes tends to place individuals at greater risk for heat-related illness during heat waves and physical activity due to an impaired capacity to dissipate heat. Specifically, individuals with diabetes have been reported to have lower skin blood flow and sweating responses during heat exposure and this can have important consequences on cardiovascular regulation and glycemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
151
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 204 publications
(181 citation statements)
references
References 186 publications
4
151
3
3
Order By: Relevance
“…46 The implications for such a deficiency are wide ranging and may increase susceptibility to metabolic disease, 46,47 impaired vascular function 48 and even contribute to the impaired thermoregulatory control evident in individuals with diabetes. 49 While there were no clear differences in the HSP70 response between either PH or EX, there were clear differences in the IL-6 response. Previous work has shown that temperature increases independently elevate IL-6.…”
Section: Discussionmentioning
confidence: 92%
“…46 The implications for such a deficiency are wide ranging and may increase susceptibility to metabolic disease, 46,47 impaired vascular function 48 and even contribute to the impaired thermoregulatory control evident in individuals with diabetes. 49 While there were no clear differences in the HSP70 response between either PH or EX, there were clear differences in the IL-6 response. Previous work has shown that temperature increases independently elevate IL-6.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, diabetes has been linked to impairments in temperature control during exposure to thermal stress (43). Our studies reveal a direct link between temperature regulation and metabolism, indicating that a uridine-centered model of energy homeostasis may pave the way for future studies on uridine homeostasis and diabetes as well as other metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, restoring purinergic receptor function might help preserve or re‐establish near‐normal levels of skin perfusion, which represents an important avenue of heat dissipation during heat stress. T2D is associated with higher rates of heat illness and death during heat stress when compared with the general population (Kenny et al., ; Kenny, Yardley, Brown, Sigal, & Jay, ).…”
Section: Discussionmentioning
confidence: 99%